The Association between Marketing Mix and Decision Process for Choosing Outpatient Health Services - Farantika, Dwiki Yessi; Witcahyo, Eri; Utami, Sri (Unnes Journal of Public Health, 2019)
Abstract The hospital marketing mix is ??a set of marketing tools used by hospitals in influencing and knowing the response of service buyers. Dr. Abdoer Rahem Situbondo Regional General Hospital experienced a decrease in the number of patient visits over the past three years from 2014 to 2016, respectively 59,537, 53,720 and 47,699. This shows that patient loyalty is reduced. This study aimed to analyze the marketing mix association with the decision process of choosing outpatient health services at Dr. Abdoer Rahem Situbondo Regional General Hospital. The type of research used is analytic with cross-sectional design. Samples of 94 people were taken by systematic random sampling technique and analyzed using the contingency coefficient test with a confidence level of 95%. The results of this study were that type of employment, product mix, price mix, and promotion mix had weak association with the decision process of choosing outpatient health services. While variables that were not associated with the decision process of choosing outpatient health services were age, gender, education level, monthly income and place mix. The conclusion of this study was that the hospital can focus on improving product mix, price mix, and promotion mix.    Abstrak Bauran pemasaran rumah sakit merupakan seperangkat alat pemasaran yang digunakan rumah sakit dalam mempengaruhi dan mengetahui tanggapan pembeli pelayanan. RSUD dr. Abdoer Rahem mengalami penurunan  jumlah kunjungan pasien lama selama tiga tahun terakhir dari tahun 2014 hingga 2016 secara berturut turut 59.537, 53.720 dan 47.699. Hal ini menunjukkan loyalitas dari pasien berkurang. Penelitian ini bertujuan untuk menganalisis hubungan bauran pemasaran dengan proses keputusan memilih pelayanan kesehatan rawat jalan RSUD dr. Abdoer Rahem Situbondo. Jenis penelitian yang digunakan adalah analitik dengan design cross sectional yang. Sampel sebanyak 94 orang yang diambil dengan teknik systematic random sampling dan dianalisis menggunakan uji koefisien kontingensi dengan tingkat kepercayaan 95%. Hasil penelitian ini adalah ada hubungan yang lemah antara jenis pekerjaan, bauran produk, bauran harga, dan bauran promosi dengan proses keputusan memilih pelayanan kesehatan rawat jalan. Sedangkan variabel yang tidak berhubungan dengan proses keputusan memilih pelayanan kesehatan rawat jalan adalah umur, jenis kelamin, tingkat pendidikan, pendapatan per bulan dan bauran tempat. Kesimpulan penelitian ini adalah pihak rumah sakit dapat berfokus pada pembenahan bauran produk, bauran harga, dan bauran promosi.